Care, Healing, and, Human Well-Being within Interreligious Discourses - Weiss, Helmut; Federschmidt, Karl H.; Louw, Daniël; Bredvik, Linda Sauer (African Sun Media, 2021)
Care, Healing, and Human Well-Being within Interreligious Discourses is an edited, peer reviewed volume of global perspectives on interreligious approaches to healing and well-being by 23 academics and practitioners from five different faith practices and 13 different cultures. With chapters by counsellors, chaplains, religious thinkers and linguists, the multifaceted nature of the volume provides an expansive approach to spiritual care and counselling.In order to understand the ways in which interreligious encounters can have an enriching effect on our humanity, the volume is divided into four sections that address: methodological questions surrounding spiritual caregiving, perspectives of different faith traditions on care and healing, the challenges to the praxis of care in diverse cultural and political settings and, finally, how spiritual care and healing can be carried out in public places such as the police, the military, and hospitals. The book is an outgrowth of 25 years of experience within the Society for Interreligious Care and Counselling (SIPCC) to promote better understanding and practices of intercultural and interreligious spiritual caregiving.